Gender determination from fingerprints - Karki, RK; Singh, PK (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: Fingerprints are one of the most mature biometric technologies and are considered legitimate proofs of evidence in courts of law for human identification all over the world. There is relatively less research has been done for its use in this field of gender identification. Hence, the present study was done to look the correlation between fingertip patterns with the gender of an individual. METHODS: Study was carried out over a period of one month among 200 medical students (100 male & 100 female) belonging to the age group 18-25 years of Kathmandu University School of Medical Sciences, Dhulikhel, Kavre. RESULTS: Each finger print is unique; loops are the most commonly occurring fingerprint pattern while arches are the least common. Males have a higher incidence of whorls and females have a higher incidence of loops. CONCLUSION: We can conclude that there is an association between distribution of fingerprint patterns and gender and thus prediction of gender of a person is possible based on his fingerprint pattern. DOI: http://dx.doi.org/10.3126/jucms.v2i1.10484 Journal of Universal College of Medical Sciences (2014) Vol.2(1): 12-15